2015
DOI: 10.5665/sleep.4906
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Waist Circumference in Adults: A Meta-Analysis

Abstract: Internationally, cross-sectional studies demonstrate a significant negative relation between sleep duration and waist circumference, indicating shorter sleep durations covary with central adiposity. Future research should include prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 47 publications
(97 reference statements)
7
58
0
3
Order By: Relevance
“…In our study, sleeping more than 7 h/day was associated with a lower risk of OB and AO, and the risk was even lower sleeping more than 8 h/day. These data agree with other studies that found an association between shorter sleeping time and the risk of OB [7] and AO [8]. However, results of other studies that have considered other indicators of AO are controversial [26]; the association between sleep and obesity may be more linear in young adults and weaker in older adults [39].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, sleeping more than 7 h/day was associated with a lower risk of OB and AO, and the risk was even lower sleeping more than 8 h/day. These data agree with other studies that found an association between shorter sleeping time and the risk of OB [7] and AO [8]. However, results of other studies that have considered other indicators of AO are controversial [26]; the association between sleep and obesity may be more linear in young adults and weaker in older adults [39].…”
Section: Discussionsupporting
confidence: 90%
“…Obesity is the result of an imbalance between energy intake and expenditure where genetic, physiological and environmental factors are also involved [3], Apart from sex and age, which has shown to be related to obesity [2], other potential confounders of this association in adults include the socioeconomic status (SES) [4,5], physical inactivity [6], sleeping time [7,8] and smoking habits [9]. …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of both cross-sectional and longitudinal studies also supports a consistent association between short sleep duration and concurrent as well as future obesity [4]. During the current review period, another meta-analysis on a total of 56,259 participants reported a significant negative association between sleep duration and waist circumference, indicating shorter sleep durations co-vary with central adiposity [5]*. This relationship appears stronger in children and young adults than in older adults.…”
Section: Introductionmentioning
confidence: 54%
“…An association between poor sleep quality and increased WC but not increased BMI was found, which is confirmed in a systematic review [9]. This difference between increased BMI and WC may be related to the different mechanisms at play with each type of obesity [32].…”
Section: Discussionmentioning
confidence: 72%